2019
DOI: 10.1097/md.0000000000016029
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/NF-κB signaling pathway gene single nucleotide polymorphisms alter gene expression levels and affect ARDS occurrence and prognosis outcomes

Abstract: Background: To study the occurrence and prognosis of acute respiratory distress syndrome (ARDS) using single nucleotide polymorphisms (SNPs) of TNF-α rs1800629, IL-6 rs1800796, and MyD88 rs7744 loci in the TLR4/NF-κB pathway. Methods: Genotypes were analyzed for TNF-α rs1800629, IL-6 rs1800796, and MyD88 rs7744… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…This suggests that the inflammatory signalling pathway was activated and involved in kidney damage, which is consistent with the results of Garibotto et al [9]. The activation of TLR4 can lead to the translocation of NF-kB (p65) to the nucleus, thereby resulting in the activation of downstream NLRP3 protein [10][11][12][13] and inducing the inflammatory response. Some specific microRNAs play a crucial role in the fibrosis process of tissues [14,15].…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that the inflammatory signalling pathway was activated and involved in kidney damage, which is consistent with the results of Garibotto et al [9]. The activation of TLR4 can lead to the translocation of NF-kB (p65) to the nucleus, thereby resulting in the activation of downstream NLRP3 protein [10][11][12][13] and inducing the inflammatory response. Some specific microRNAs play a crucial role in the fibrosis process of tissues [14,15].…”
Section: Discussionsupporting
confidence: 88%
“…In the non-Asian group, GC and GG+GC genotype were risk factors for the development of liver diseases, which was in line with some studies showing the mRNA expressions of IL-6 was higher in the rs1800796 GG genotype compare with others. [45,53] rs1800797 (-579 G/A) is also another polymorphism located within the promoter region of IL-6 gene. Our overall, non-Asian subgroup analysis and the study of Chang et al, [42] showed GG and GA genotype may be risk factors for liver diseases, indicating patients with these genotypes may have higher IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…This effect leads to increased inflammatory gene expression and pro-survival gene expression, which may prolong the viral permanence in the infected cell [136]. (4) Upon recognition of viral particles and LPS from bacteria, TLR4-mediated signaling may lead to increased deleterious inflammation via NF-kB recruitment and p38 phosphorylation [105,106]. TLR4 polymorphism might explain the differential susceptibility to ARDS in COVID-19 patients [106].…”
Section: Respiratory Systemmentioning
confidence: 99%
“…During acute lung injury, the presence of TLR4 in macrophages acts as a key factor mediating the severity of the inflammation as well as tissue damage [105]. TLR4 polymorphisms have been also correlated to poor ARDS prognosis [106]. Many viruses, such as influenza and rhinoviruses, rely on strategies to silently surpass TLR-based warning signal in the airway epithelium, via inhibition of proteins such as RIG-1 and MDA5, components of TLR4 signaling and IRF-3, to drive IFN production [97].…”
Section: Respiratory Systemmentioning
confidence: 99%